2017
DOI: 10.1002/path.4839
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal androgen receptor/interleukin‐6 crosstalk drives oesophageal carcinoma progression and contributes to patient prognosis

Abstract: Oesophageal squamous cell carcinoma (ESCC), a leading lethal malignancy of the digestive tract, is characterized by marked gender disparity. Clarifying the roles of the function and regulatory pathway of the androgen receptor (AR) will improve our understanding of oesophageal cancer progression, thereby facilitating the personalized management of ESCC. Here we report evidence to show that AR is a key mediator of inflammatory signals in ESCC cancer progression. High AR expression was associated with poor overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 66 publications
0
39
0
Order By: Relevance
“…Given the marked gender disparity in incidence and clinical outcomes of human ESCC, one intriguing question is how sex steroid signaling pathways are involved in the regulation of ESCC oncogenesis and progression . We and others have previously shown that AR and ERβ signaling pathways play important roles in tumorigenesis and progression of esophageal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the marked gender disparity in incidence and clinical outcomes of human ESCC, one intriguing question is how sex steroid signaling pathways are involved in the regulation of ESCC oncogenesis and progression . We and others have previously shown that AR and ERβ signaling pathways play important roles in tumorigenesis and progression of esophageal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The cylindrical tumor cores were punched and transferred to the recipient block using a 2.0‐mm diameter precision punch. Blocks of the tissue microarray (TMA) were cut into 4‐μm sections and processed for IHC as described previously . TMA slides were incubated with anti‐NCOA1 antibody (sc‐8995, Santa Cruz) at room temperature for 1 hour followed by incubation with the HRP‐conjugated secondary antibody at room temperature for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In esophageal adenocarcinoma, AR-dependent androgen signaling suppressed cell proliferation [81] whereas estrogen signaling (through both ERα and ERβ) promoted the cell growth [82, 83]. In contrast, in esophageal squamous cell carcinoma, AR-dependent androgen signaling promoted the cell growth and migration [8486] whereas whether estrogen signaling suppressed the cell growth through ERα or ERβ was under the debate [85, 8791]. These studies have been mainly conducted in human esophageal cancer cell lines.…”
Section: Summary Of Findingsmentioning
confidence: 99%